Pain in Medieval and Modern Contexts - Trembinski, Donna (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
Intellectual historians of the High Middle Ages have generally argued that scholastic medicine had little influence on the study of theology in medieval universities, especially in the thirteenth century. Yet three chairs of theology at the University of Paris in the early 1200s had previous careers as physicians. Their extant work suggests that they did turn to their medical roots to explicate theological problems, sometimes rarely, as in the work of Guerric of St. Quentin, but sometimes more often as in the work of Roland of Cremona. Indeed Roland’s work on human and divine emotions, including his discussions of sadness and pain, demonstrates that Roland was dedicated to integrating his medical learning into his theological arguments and to ensuring that the positions of his medical training were in agreement with the theological arguments he made. A short conclusion suggests historiographical reasons for why the medical influence on early Parisian theological treatises has generally been overlooked, pointing to the separate nature of study of mind and body that has occurred since the rise of Cartesian dualism in the seventeenth century.